2019
DOI: 10.1186/s12881-019-0909-5
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation is highly correlated with differential gene expression: a pan-cancer study

Abstract: BackgroundCancer is a heterogeneous disease with many genetic variations. Lines of evidence have shown copy number variations (CNVs) of certain genes are involved in development and progression of many cancers through the alterations of their gene expression levels on individual or several cancer types. However, it is not quite clear whether the correlation will be a general phenomenon across multiple cancer types.MethodsIn this study we applied a bioinformatics approach integrating CNV and differential gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
153
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(191 citation statements)
references
References 58 publications
18
153
1
Order By: Relevance
“…CNAs change the dosage of affected genes and can lead to transcriptome changes 58 . We sought to determine whether ancestry-associated CNAs have such downstream mRNA associations.…”
Section: Changesmentioning
confidence: 99%
“…CNAs change the dosage of affected genes and can lead to transcriptome changes 58 . We sought to determine whether ancestry-associated CNAs have such downstream mRNA associations.…”
Section: Changesmentioning
confidence: 99%
“…It has been demonstrated that modulating gene expression is one of the most important ways for CNV to play diversi ed roles in diseases [11][12][13][14]. In this study, the results showed that 5022 gene expressions in TCGA were signi cantly modulated by CNV (p <0.05, adjusted p <0.2) and 577 genes in TARGET were signi cantly associated with CNV (p <0.05, adjusted p <0.2).…”
Section: Integrative Analysis Of Gene Expressions In Concordance Withmentioning
confidence: 58%
“…However, the evolutionary advantage of CNAs is based on the expression of particular genes located within the CNA genomic region. Therefore, analysis of gene expression data provides additional valuable information [20][21][22][23][24] . Some among the list of the consistently co-expressed genes, including the first and the last when sorted in terms of their genomic location, play some role in tumorigenesis and it is possible that this role is due to their synergistic functions.…”
Section: Analysis Of Large Gene Expression Datasets From Biopsies Of mentioning
confidence: 99%